2003
DOI: 10.1086/379321
|View full text |Cite
|
Sign up to set email alerts
|

Is Methicillin-Resistant Staphylococcus aureus More Virulent than Methicillin-Susceptible S. aureus? A Comparative Cohort Study of British Patients with Nosocomial Infection and Bacteremia

Abstract: Staphylococcus aureus is the most common cause of hospital-acquired bacteremia. From 1995 through 2000, data on age, sex, patient specialty at time of first bacteremia, primary and secondary sites of infection, delay in initiating antimicrobial therapy, and patient outcome were prospectively recorded for 815 patients with nosocomial S. aureus bacteremia. The proportion of patients whose death was attributable to methicillin-resistant S. aureus (MRSA) was significantly higher than that for methicillin-susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
122
2
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(141 citation statements)
references
References 34 publications
8
122
2
9
Order By: Relevance
“…In another meta-analysis, Whitby et al (2001) observed that bacteraemia caused by MRSA was associated with significantly higher mortality rates than bacteraemia caused by MSSA (29 % vs 12 %). The associated proportion of patients whose death was attributable to MRSA was significantly higher than that for MSSA [11.8 % vs 5.1 %; odds ratio (OR) 2.49] (Melzer et al, 2003). Bacteraemia due to MRSA is associated with both an increase in median hospital length of stay (9 days compared with 7 days) and consequently higher median hospital charges (US$ 26 424 vs US$ 19 212) (Melzer et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another meta-analysis, Whitby et al (2001) observed that bacteraemia caused by MRSA was associated with significantly higher mortality rates than bacteraemia caused by MSSA (29 % vs 12 %). The associated proportion of patients whose death was attributable to MRSA was significantly higher than that for MSSA [11.8 % vs 5.1 %; odds ratio (OR) 2.49] (Melzer et al, 2003). Bacteraemia due to MRSA is associated with both an increase in median hospital length of stay (9 days compared with 7 days) and consequently higher median hospital charges (US$ 26 424 vs US$ 19 212) (Melzer et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The associated proportion of patients whose death was attributable to MRSA was significantly higher than that for MSSA [11.8 % vs 5.1 %; odds ratio (OR) 2.49] (Melzer et al, 2003). Bacteraemia due to MRSA is associated with both an increase in median hospital length of stay (9 days compared with 7 days) and consequently higher median hospital charges (US$ 26 424 vs US$ 19 212) (Melzer et al, 2003).The treatment of MSSA bacteraemia with vancomycin is associated with treatment failure and higher mortality rates compared with treatment with b-lactam antibiotics In patients with MSSA-associated bacteraemia, Kim et al (2008) showed in a retrospective cohort study a mortality rate of 37 % in patients treated with vancomycin versus a mortality rate of 18 % in patients treated with b-lactam antibiotics. In a patient population with MSSA-associated infective endocarditis, Lodise et al (2007) showed that the mortality rate in patients who received empirical vancomycin was signifcantly higher (39.4 %) than he mortality rate of 11.4 % in patients who received empirical b-lactam therapy.…”
mentioning
confidence: 99%
“…MRSA SSI are disastrous and lead to adverse health outcomes and higher rates of complications in orthopaedic patients [7,8]. SSI with MRSA increases post-operative hospital stay by two weeks, doubles hospitalization rates, and triples overall care costs [7,8,17].…”
Section: Discussionmentioning
confidence: 99%
“…Preoperative nasal colonization with SA has been shown to be a strong risk factor for SSI, with carriers being two to nine times more likely than non-carriers to acquire SSI [1,[3][4][5][6]. Methicillin-resistant SA (MRSA) infection provides particularly difficult complications following surgical procedures and has been documented to be twice as deadly as methicillin-sensitive SA (MSSA) in SSI [7,8]. MRSA follows similar trends of SSI as Methicillin-sensitive SA, with preoperative MRSA positive carriers being at higher risk of SSI as opposed to MRSA negative patients [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation